2017
DOI: 10.21873/anticanres.12122
|View full text |Cite
|
Sign up to set email alerts
|

Liprin-α4 as a Possible New Therapeutic Target for Pancreatic Cancer

Abstract: Liprin-α4 plays a pivotal role in inducing malignant phenotypes such as increased proliferation and invasion in pancreatic cancer, and that liprin-α4 could be a new effective therapeutic target for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…MiR-34a, a tumor suppressor miRNA, inhibited the progressive phenotypes of PCa cells via directly regulating STMN1 (45). PPFIA4 belongs to the liprin-alpha gene family and inhibition of PPFIA4 reduced pancreatic cancer cell proliferation and invasion (46). Moreover, suppression of PPFIA4 promoted chemosensitivity of small lung cancer (SCL) cells under hypoxia (47).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-34a, a tumor suppressor miRNA, inhibited the progressive phenotypes of PCa cells via directly regulating STMN1 (45). PPFIA4 belongs to the liprin-alpha gene family and inhibition of PPFIA4 reduced pancreatic cancer cell proliferation and invasion (46). Moreover, suppression of PPFIA4 promoted chemosensitivity of small lung cancer (SCL) cells under hypoxia (47).…”
Section: Discussionmentioning
confidence: 99%
“…Within those DEGs unique to control-iPSC, we found PPFIA4 (also known as Liprin-α4), ceruloplasmin (CP), and stanniocalcin-1 (STC1), which were increased 13.6-fold, 77-fold, and fivefold, respectively, under 2% oxygen, only in control iPSC-derived trophoblast ( Supplementary Figure 4). Both liprin-α4 and STC1 have been shown to promote invasion of cancer cells [51][52][53] , while secretion of ceruloplasmin in the placenta is known to be induced by hypoxia 54 . Another interesting gene in this group was ARNT (aryl hydrocarbon receptor nuclear translocator; also called "HIF1β"), which showed a statistically-significant (adjusted p value < 0.05), albeit modest (1.3-fold), increase only in control-iPSC ( Supplementary Figure 4).…”
Section: Global Gene Expression In Pe and Control Ipsc-derived Trophomentioning
confidence: 99%
“…Moreover, As the intracellular effectors of receptor protein tyrosine phosphatase-leukocyte antigen related receptor F (LAR-RPTP), PPFIA4 interacts with the catalytically inactive D2 domain of LAR-RPTP via their highly conserved C-terminal three sterile alpha motif domains and promotes its phosphatase activity [ 49 ]. There is emerging evidence indicating that PPFIA4 plays an important role in several malignancies including refractory pancreatic cancer [ 20 ], small cell lung cancer [ 21 ], and clear cell renal cell cancer [ 18 ]. In this study, we clearly demonstrated that PPFIA4 could promote CRPC progression by enhancing the mitochondrial function of PCa cells and served as a novel regulator for mitochondrial function in CRPC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Liprin-α4 (encoded by PPFIA4), a member of liprin-α family, has been found in various multiprotein complexes [ 18 , 19 ]. It has been reported as a new potential therapeutic target for refractory pancreatic cancer [ 20 ], small cell lung cancer [ 21 ], and clear cell renal cell cancer [ 18 ]. Additionally, PPFIA4 has been reported in several studies to be potentially associated with aberrant metabolic processes [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%